Dementia‐related adverse events in PARADIGM‐HF and other trials in heart failure with reduced ejection fraction. (20th November 2016) - Cannon, Jane A.; Shen, Li; Jhund, Pardeep S.; Kristensen, Søren L.; Køber, Lars; Chen, Fabian; Gong, Jianjian; Lefkowitz, Martin P.; Rouleau, Jean L.; Shi, Victor C.; Swedberg, Karl; Zile, Michael R.; et al.
Abstract : Aims: Inhibition of neprilysin, an enzyme degrading natriuretic and other vasoactive peptides, is beneficial in heart failure with reduced ejection fraction (HFrEF), as shown in PARADIGM‐HF which compared the angiotensin receptor–neprilysin inhibitor (ARNI) sacubitril/valsartan with enalapril. As neprilysin is also one of many enzymes clearing amyloid‐β peptides from the brain, there is a theoretical concern about the long‐term effects of sacubitril/valsartan on cognition. Therefore, we have examined dementia‐related adverse effects (AEs) in PARADIGM‐HF and placed these findings in the context of other recently conducted HFrEF trials. Methods and results: In PARADIGM‐HF, patients with symptomatic HFrEF were randomized to sacubitril/valsartan 97/103 mg b.i.d. or enalapril 10 mg b.i.d. in a 1:1 ratio. We systematically searched AE reports, coded using the Medical Dictionary for Regulatory Activities (MedDRA), using Standardized MedDRA Queries (SMQs) with 'broad' and 'narrow' preferred terms related to dementia. In PARADIGM‐HF, 8399 patients aged 18–96 years were randomized and followed for a median of 2.25 years (up to 4.3 years). The narrow SMQ search identified 27 dementia‐related AEs: 15 (0.36%) on enalapril and 12 (0.29%) on sacubitril/valsartan [hazard ratio (HR) 0.73, 95% confidence interval (CI) 0.33–1.59]. The broad search identified 97 (2.30%) and 104 (2.48%) AEs (HR 1.01, 95% CI 0.75–1.37), respectively. The rates of dementia‐related AEs in both treatment groups in PARADIGM‐HF were similar to those in three other recent trials in HFrEF. Conclusion: We found no evidence that sacubitril/valsartan, compared with enalapril, increased dementia‐related AEs, although longer follow‐up may be necessary to detect such a signal and more sensitive tools are needed to detect lesser degrees of cognitive impairment. Further studies to address this question are warranted.